DIGITALIZATION OF LIBRARIES: ISSUES & CHALLENGES (International Journal of Food and Nutritional Sciences, 2022)
This has led to the creation and use of digital libraries, which offer several advantages over traditional libraries. Digital libraries can store vast amounts of information in a compact digital format, making it possible to access and distribute them easily without the need for physical storage space. Additionally, digital libraries offer faster access to information, and users can search and access data from anywhere and at any time. However, the implementation of digital libraries is not without challenges. One of the primary issues is the cost of digitizing and maintaining the materials, IT infrastructure, and software to support the library. In addition, the process of digitizing materials may require significant resources in terms of time, finances, and personnel. Furthermore, issues such as copyright and intellectual property rights have to be taken into consideration when digitizing the materials. It is important to ensure that the library materials have appropriate licenses and legal permissions to avoid copyright infringement. Preservation and security of digital materials is also a critical challenge. Digital materials are vulnerable to loss and damage due to technical issues such as system failures, hardware or software failures, virus, or cyber-attacks. Digital libraries also face challenges in providing adequate user support and training to ensure that users can access and navigate the library materials appropriately. Users need to be able to understand the search and retrieval systems and have the skills needed to navigate the library's interfaces and online content. In conclusion, digital libraries offer significant benefits and opportunities for information access and dissemination. However, they also face significant challenges, including cost, copyright and intellectual property issues, preservation and security of digital materials, and user support and training. While these challenges are not insurmountable, they require careful consideration and planning in the implementation of digital library services.